Antibody response and safety of inactivated SARS-CoV-2 vaccines in chronic hepatitis B patients with and without cirrhosis - Huanhuan Cao; Huanhuan Cao; Huanhuan Cao; Huanhuan Cao; Huanhuan Cao; Yufei Huang; Yufei Huang; Yufei Huang; Yufei Huang; Chunxiu Zhong; Chunxiu Zhong; Chunxiu Zhong; et al. (Frontiers in Immunology, 2023)
BackgroundThe immune response and safety of inactivated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines among patients with chronic hepatitis B (CHB), especially those with cirrhosis, are not clear. Therefore, this study was conducted to evaluate the efficacy and safety of inactivated SARS-CoV-2 vaccines among CHB patients with and without cirrhosis.Patients and methodsA total of 643 CHB patients who received two doses of inactivated SARS-CoV-2 vaccines (BBIBP-CorV and CoronaVac) were enrolled. Serum samples were collected and tested for SARS-CoV-2 S-receptor-binding domain (S-RBD) immunoglobulin G (IgG) at enrollment. Data on adverse events (AEs) within 7 days after the second dose were obtained using a questionnaire.ResultsA total of 416 non-cirrhotic and 227 cirrhotic patients were included in the analysis. Cirrhotic patients had lower antibody titers than non-cirrhotic patients after adjusting for age, sex, and time interval (2.45 vs. 2.60 ng/ml, p = 0.034). Furthermore, the study revealed that cirrhotic patients demonstrated a slower rate of seropositivity increase, with the highest rate being recorded at week 4 and reaching 94.7%. On the other hand, among non-cirrhotic patients, the seropositivity rate peak was observed at week 2 and reached 96.0%. In addition, cirrhotic patients displayed a more rapid decline in the seropositivity rate, dropping to 54.5% after ≥16 weeks, while non-cirrhotic patients exhibited a decrease to 67.2% after the same time period. The overall incidence of AEs was low (18.4%), and all AEs were mild and self-limiting. In addition, 16.0% of participants had mild liver function abnormalities, and half of them returned to normality within the next 6 months without additional therapy. The participants who experienced liver function abnormalities showed a higher seropositivity rate and antibody titer than those who did not (91.6% vs. 79.5%, p = 0.005; 2.73 vs. 2.41 ng/ml, p < 0.001).ConclusionCirrhotic CHB patients had lower antibody titers to inactivated SARS-CoV-2 vaccines than non-cirrhotic patients. The vaccines were generally well tolerated in both non-cirrhotic and cirrhotic CHB patient groups. Patients with abnormal liver function may have a better antibody response than those without.